The use of information and communication technologies in physical education: modern approaches to health promotion - S. V. Kozin; N. V. Ivaniuta; V. P. Radziievskyi (Scientific Journal of National Pedagogical Dragomanov University Series 15 Scientific and pedagogical problems of physical culture (physical culture and sports), 2026)
This article presents the results of a review and analytical study of contemporary approaches to the use of information and communication technologies (ICT) in the physical education of schoolchildren and students. The relevance of the study stems from the digital transformation of education, the need to increase the level of physical activity among children and young people, and the search for effective health-promoting technologies in the context of the modernisation of the educational process. The aim of the study is to summarise contemporary scientific approaches to the use of information and communication technologies in physical education and to determine their role in fostering a healthy lifestyle and health-promoting competence among schoolchildren and students. Research methods: content analysis of contemporary academic literature on the subject under investigation; comparison of the results of Ukrainian and international studies. This paper analyses the potential for using mobile applications, wearable digital devices, online platforms, gamification and exergaming technologies, virtual and augmented reality, as well as artificial intelligence systems in physical education. It has been established that the comprehensive application of modern digital technologies contributes to increasing levels of physical activity, developing motivation to learn, and fostering self-control skills and a healthy lifestyle. At the same time, the effectiveness of ICT use depends on the teacher’s pedagogical skills, the level of digital competence of those involved in the educational process, the material and technical resources available to educational institutions, and the methodologically sound implementation of digital technologies.